Ukrainian model of cooperation between social education and social works - BEHAL, ONYSYA MYKILAIVNA (Journal of Education, Technology and Computer Science, 2016)
The articles provides philosophic analysis of the core of social works as the component ofeducational and up-bringing process. The author researched the nature and the function of it, itsrole in the formation of outlook culture of modern youth as students. The author also observes thecooperation between social work and social education on the example of Ukrainian model. Theauthor investigated conditions and means of organic combination of social work and educationaland up-bringing process.